Fundamental concepts of protein therapeutics and spacing in oncology: an updated comprehensive review - Far, Bahareh Farasati; Safaei, Maryam; Mokhtari, Fatemeh; Fallahi, Mohammad Sadegh; Naimi-Jamal, Mohammad Reza (Humana Press Inc, 2023)
Current treatment regimens in cancer cases cause significant side effects and cannot effectively eradicate the advanced disease. Hence, much effort has been expended over the past years to understand how cancer grows and responds to therapies. Meanwhile, proteins as a type of biopolymers have been under commercial development for over three decades and have been proven to improve the healthcare system as effective medicines for treating many types of progressive disease, such as cancer. Following approving the first recombinant protein therapeutics by FDA (Humulin), there have been a revolution for drawing attention toward protein-based therapeutics (PTs). Since then, the ability to tailor proteins with ideal pharmacokinetics has provided the pharmaceutical industry with an important noble path to discuss the clinical potential of proteins in oncology research. Unlike traditional chemotherapy molecules, PTs actively target cancerous cells by binding to their surface receptors and the other biomarkers particularly associated with tumorous or healthy tissue. This review analyzes the potential and limitations of protein therapeutics (PTs) in the treatment of cancer as well as highlighting the evolving strategies by addressing all possible factors, including pharmacology profile and targeted therapy approaches. This review provides a comprehensive overview of the current state of PTs in oncology, including their pharmacology profile, targeted therapy approaches, and prospects. The reviewed data show that several current and future challenges remain to make PTs a promising and effective anticancer drug, such as safety, immunogenicity, protein stability/degradation, and protein-adjuvant interactions.
Keywords: Cancer therapy; Protein therapeutics; Targeted therapy; Biotherapeutics